What's the Special Lines?

Calculus Level 3

There are two lines which are both tangent and normal to the curve x = ( y + 1 ) 2 3 + 1 x = (y + 1)^{\frac{2}{3}} + 1 .

If the two lines intersect at ( x 0 , y 0 ) (x_{0},y_{0}) and x 0 + y 0 = a b x_{0} + y_{0} = \dfrac{a}{b} , where a a and b b are coprime positive integers, find a + b a + b .


The answer is 35.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
Oct 6, 2018

Let y = t 3 1 x = t 2 + 1 d y d x ( t = t 1 ) = 3 2 t 1 y = t^3 - 1 \implies x = t^2 + 1 \implies \dfrac{dy}{dx}|(t = t_{1}) = \dfrac{3}{2}t_{1} \implies the tangent line to the curve at ( x ( t 1 ) , y ( t 1 ) ) (x(t_{1}),y(t_{1})) is: y ( t 1 3 1 ) = 3 2 t 1 ( x ( t 1 2 + 1 ) ) y - (t_{1}^3 - 1) = \dfrac{3}{2}t_{1}(x - (t_{1}^2+ 1))

Let the line be normal to the curve at ( x ( t 2 ) , y ( t 2 ) ) ( t 2 t 1 ) ( t 2 2 + t 1 t 2 + t 1 2 ) = 3 2 t 1 ( t 2 t 1 ) ( t 2 + t 1 ) 1 2 ( t 2 t 1 ) ( 2 t 2 2 t 1 t 2 t 1 2 ) = 0 (x(t_{2}),y(t_{2})) \implies (t_{2} - t_{1})(t_{2}^2 + t_{1}t_{2} + t_{1}^2) = \dfrac{3}{2}t_{1}(t_{2} - t_{1})(t_{2} + t_{1}) \implies \dfrac{1}{2}(t_{2} - t_{1})(2t_{2}^2 - t_{1}t_{2} - t_{1}^2) = 0 t 1 t 2 t 2 = t 1 2 t_{1} \neq t_{2} \implies t_{2} = -\dfrac{t_{1}}{2}

Since the tangent is also normal to the curve at ( x ( t 2 ) , y ( t 2 ) ) 9 4 t 1 t 2 = 1 (x(t_{2}),y(t_{2})) \implies \dfrac{9}{4}t_{1}t_{2} = -1 9 8 t 1 2 = 1 t 1 = ± 2 2 3 \implies \dfrac{9}{8}t_{1}^2 = 1 \implies t_{1} = \pm\dfrac{2\sqrt{2}}{3} \implies the two slopes are ± 2 \pm\sqrt{2} .

slope = 2 = \sqrt{2} and t 1 = 2 2 3 y 0 2 x 0 = 35 2 27 27 t_{1} = \dfrac{2\sqrt{2}}{3} \implies y_{0} - \sqrt{2}x_{0} = \dfrac{-35\sqrt{2} - 27}{27}

slope = 2 = -\sqrt{2} and t 2 = 2 3 y 0 + 2 x 0 = 35 2 27 27 t_{2} = \dfrac{\sqrt{2}}{3} \implies y_{0} + \sqrt{2}x_{0} = \dfrac{35\sqrt{2} - 27}{27}

y 0 = 1 \implies y_{0} = -1 and x 0 = 35 27 x 0 + y 0 = 35 27 1 = 8 27 = a b a + b = 35 x_{0} = \dfrac{35}{27} \implies x_{0} + y_{0} = \dfrac{35}{27} - 1 = \dfrac{8}{27} = \dfrac{a}{b} \implies a + b = \boxed{35} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...